Drink from a waterfall : challenges of having autistic children on communication and social behavior / Mohd Yusof Zulkefli and Norfishah Mat Rabi - Mohd Yusof, Zulkefli; Norfishah, Mat Rabi (Universiti Teknologi MARA, Perak, 2018)
Socialising and communicating can be challenges for many autistic kids. Communication difficulties among autistic are very common. Some of them can speak very fluently whereas there are also facing with speech impaired to varying degrees and there have kids with ASD who are unable to speak at all. To those who can speak, they will often use language in a limited or unusual way (Foggo & Webster, 2017). Therefore, it will disturb the way they interact with others hence will making them behave abnormally. This study was undertaken to analyse the challenges of having autism kid towards communication and social behaviour. Objectives of this research is to find out the communication and social behaviour problem that occur among ASD children and at the same time to find out the best solutions to overcome this matter. Data were obtained from an in-depth interview with parents who lived with diagnosed autistic children, special education teachers, and caregivers. Observations were made to understand their communication cues.